Personal Gambling Expectancies among Asian American and White American College Students - Chan, Alan Ka Ki (2015)
Many college students are involved in gambling behavior as a recreational activity. Their involvement could potentially develop into problem gambling, an issue of increasing concern to student health. At the same time, evidence suggests that Asian Americans are overrepresented amongst problem gamblers in this age period. Research on factors related to initiation and development of problem gambling in college students is necessary to inform the development of effective and culturally-sensitive prevention efforts against gambling. The relationships between personal gambling expectancies at two levels of specificity (two general and six specific types of expectancies) and college student gambling at two levels of behavior (initiation and problems) were examined in a sample of 813 Asian American and White American college students. The study aimed to address (a) whether expectancies explained ethnic differences in gambling, (b) ethnic similarities and differences in the pattern of relationships between expectancies and gambling, and (c) whether expectancies that emerged in both ethnic groups have a greater risk or protective effect for one group than another. Results showed that Asian American students reported more problem gambling than White American students, but expectancies did not account for this group difference. Risk and protective factors for initiation were relatively similar between groups, but different patterns of risk emerged for each group for problem gambling. Implications for college primary prevention and harm reduction programs are discussed.